The TAC paradigm: Specifying tangible user interfaces. - Shaer, Orit.; Leland, Nancy.; Calvillo-Gámez, Eduardo H.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
This paper introduces a paradigm for describing and specifying tangible user interfaces (TUIs) The proposed Token and Constraints (TAC) paradigm captures the core components of TUIs while addressing many of the conceptual challenges unique to building these interfaces. The paradigm enables the description of a broad range of TUIs by providing a common set of constructs. Thus, the TAC paradigm lays the foundation for a high-level description language and a software toolkit for TUIs. We evaluate the proposed paradigm by testing its ability to specify a wide variety of existing TUIs.